Engagement-oriented design: a study of New Zealand public cultural heritage institutions crowdsourcing platforms. Issue 4 (19th May 2020) - Johnson, Elizabeth; Liew, Chern Li
Abstract : Purpose: The purpose of this study is to propose a set of design recommendations for crowdsourcing platforms with a focus on user engagement. A sample of New Zealand (NZ) cultural heritage institutions (CHIs) crowdsourcing platforms were assessed, with the aim of offering insights into how they have been designed to encourage dialogue and engagement and to sustain participation. Design/methodology/approach: The design recommendations were derived from a review of related works. Following this, 12 crowdsourcing projects overseen by libraries, museums and an archive in NZ were assessed against the recommendations through content analysis. Findings: The recommendations were classified into four main categories. These were promote ease of use, attract and sustain user interest, foster a community of users and show users that their work is contributing to the institution and society. The findings indicated that the sample of crowdsourcing projects assessed were generally successful at displaying the credibility and significance of their projects, and promoting their crowdsourced collections. Many of the projects could nevertheless benefit from providing further support to promoting dialogues and engagement with their users and contributors and sustaining offline community interaction. Research limitations/implications: The content analysis conducted was focused on the functionality of design elements of the crowdsourcing platforms. The design recommendations derived from the analysis were intended as a starting point for discussion and they would need to be validated in further studies. Other relevant project information such as funding and staffing, promotion and outreach efforts were not solicited in this study. Such information could provide important contextualisation. Future research could take the form of in-depth case studies, including surveying those involved in the projects and stakeholders to investigate such contextual aspects of crowdsourcing projects. Originality/value: Previous research on crowdsourcing in NZ CHIs consisted of single case studies. This study provides a wider snapshot and insights into digital crowdsourcing platforms from public NZ CHIs. The study findings have practical implications for project managers and Web designers involved in crowdsourcing projects, particularly those in the cultural heritage sector.